Archiving the unspeakable : silence, memory, and the photographic record in Cambodia - Caswell, Michelle (Critical human rights., 2014)
Roughly 1.7 million people died in Cambodia from untreated disease, starvation, and execution during the Khmer Rouge reign of less than four years in the late 1970s. The regime's brutality has come to be symbolized by the multitude of black-and-white mug shots of prisoners taken at the notorious Tuol Sleng prison, where thousands of "enemies of the state" were tortured before being sent to the Killing Fields. In Archiving the Unspeakable, Michelle Caswell traces the social life of these photographic records through the lens of archival studies and elucidates how, paradoxically, they have become agents of silence and witnessing, human rights and injustice as they are deployed at various moments in time and space. From their creation as Khmer Rouge administrative records to their transformation beginning in 1979 into museum displays, archival collections, and databases, the mug shots are key components in an ongoing drama of unimaginable human suffering.--